Student Portfolio Management: The Development of the SITIMAWA Prototype - Siti Mukaromah; Arista Pratama; Eristya Maya Safitri; Ainun Rizkyani Fadillah; Zharvi Achmadha; Didan Rizky Adha (Future Science, 2023)
In response to the escalating need for efficient student portfolio management, this study introduces the development of the Student Digital Portfolio Information System (SITIMAWA) prototype. Through the utilization of Unified Modeling Language (UML) and black box testing, the research endeavors to elevate the organization and presentation of academic achievements, projects, and personal portfolios, benefiting students, instructors, and administrators alike. Executing the Waterfall methodology, the study meticulously directs the systematic design, development, and testing phases of the SITIMAWA prototype. The outcome materializes as a comprehensive system and application prototype that adeptly mirrors student portfolio management, streamlining navigation, and the coherent arrangement of academic accomplishments and personal projects. The synergistic integration of UML design and black box testing substantially fuels the success of the prototype. Conclusively, the study underscores the prowess of the Waterfall methodology in fostering a structured and methodically documented developmental process and concurrently recommends delving into further research to glean user feedback, thereby perpetuating the iterative enhancement of the SITIMAWA prototype. This endeavor aspires to forge an advanced and user-centric platform for the seamless management of student portfolios, ultimately contributing to an enriched educational experience. The ongoing refinements hold the potential to revolutionize how educational achievements are curated and presented in the digital age, enhancing engagement and collaboration within the educational ecosystem. By effectively bridging technology and education, the SITIMAWA prototype paves the way for a dynamic and transformative educational landscape.